2007
DOI: 10.1300/j073v22n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Monumentality in ‘Capital’ Cities and Its Implications for Tourism Marketing

Abstract: Monuments and monumental architecture are established vehicles for communicating capital city status. The need to reduce complex cities into simplified images also means they can be very effective destination marketing tools. This paper assesses the relationship between monuments, capital city status and tourism marketing.Monumental developments in Barcelona during two periods; 1888-1929 and 1982-present are used to explore this relationship. Barcelona provides an interesting example, because of the city's att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
(14 reference statements)
1
11
0
3
Order By: Relevance
“…Cultural heritage is often thought to be an important ingredient of city tourism ‘products’ consumed by tourists in search of the ‘authentic’ other (Tunbridge and Ashworth, 1996; Wickens, 2000; Smith, 2007). Much has been written on the economic logic which places a destination’s culture on the market, on the ‘gentrification’ of inner city areas, and the consumption of ‘symbolic’ experiences produced by the tourism and heritage industries (Alvarez Sainz, 2012; Dann, 1996; Evans, 2003; Hewison, 1987; Hooper-Greenhill, 1992; Maitland and Newman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural heritage is often thought to be an important ingredient of city tourism ‘products’ consumed by tourists in search of the ‘authentic’ other (Tunbridge and Ashworth, 1996; Wickens, 2000; Smith, 2007). Much has been written on the economic logic which places a destination’s culture on the market, on the ‘gentrification’ of inner city areas, and the consumption of ‘symbolic’ experiences produced by the tourism and heritage industries (Alvarez Sainz, 2012; Dann, 1996; Evans, 2003; Hewison, 1987; Hooper-Greenhill, 1992; Maitland and Newman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a connection between locations, broadly defined, and product attractiveness. For example, research has shown that the presentation of capital cities can be an important factor in attracting tourism, particularly because of the fact that these cities are symbols of what a country stands for (Hall, 2002; Huang and Lee, 2009; Smith, 2007). Another reason that some scholars have posited for the attractive value of capital cities is that they play an important role in conveying political power, both domestically and internationally.…”
Section: Explaining the Attractiveness Of Islamic State Photo Essaysmentioning
confidence: 99%
“…Hagia Sophia was built between 532 AD and 537 AD as the chief church of the city, located adjacent to the Great Palace. It could be understood as an example of monumentality in public art, in that it symbolises the power of the church, but also of the original rulers (Smith, 2007). Destructive forces provided the opportunity to rebuild the city, but not as a replica of the original.…”
Section: Istanbul As Constantinoplementioning
confidence: 99%
“…This drive towards monumentality in public art is often aimed at making a political statement (Lippard, 1999;Miles, 1997;Sharp et al, 2005;Sudjic, 2005). This was particularly prevalent in the nineteenth century when many of these capitals were transformed into modern urban spaces, exemplified by Haussmann's Paris (Olsen, 1986;Smith, 2007) and the desire to 'display the majesty of the nation state' (Smith, 2007, p. 80). Others are a legacy of commemorations, and help to build national identity and collective memory (Frost & Laing, 2013;Smith, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation